Comparison of robust and non-robust methods in deformation surveys - Halim Setan, 1957-; Ranjit Singh; Universiti Teknologi Malaysia. Fakulti Kejuruteraan dan Sains Geoinformasi; JSPS-VCC Seminar on Integrated Engineering (7th : 1998 : University of Malaya, Kuala Lumpur)
27